Creating connections: the role of universities in enhancing graduates' social capital and challenging nepotism. (2nd January 2020) - Gilani, David
ABSTRACT: This thought piece attempts to explore the link between graduate employment and students' social capital within the context of UK higher education. It addresses the importance of social capital and the problems faced by graduates from lower socio-economic backgrounds when applying to graduate roles. It takes a practical approach by looking at examples of initiatives within universities, including a case study from Middlesex University, that support students to make connections and grow their professional networks. It also suggests how universities can play a role in challenging the nepotism that exists within recruitment practices.